2006
DOI: 10.1523/jneurosci.0340-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Tuning of Rapid Interactions between Visual-Motion Analysis and Reaching Movement

Abstract: In addition to the goal-directed preplanned control, which strongly governs reaching movements, another type of control mechanism is suggested by recent findings that arm movements are rapidly entrained by surrounding visual motion. It remains, however, controversial whether this rapid manual response is generated in a goal-oriented manner similarly to preplanned control or is reflexively and directly induced by visual motion. To investigate the sensorimotor process underlying rapid manual responses induced by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
3

Year Published

2008
2008
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 62 publications
6
52
3
Order By: Relevance
“…It has been suggested that visuomotor control systems have spatiotemporal tunings different from those for motion perception (Amano et al 2007;Gomi et al 2006;. Indeed the present study showed directional dissociations between motion perception and OFRs, in particular for the CA-MSV stimuli, which can be ascribed at least partially to preference of the OFR responses to higher speeds.…”
Section: Comparison Between the Frequency Tuning Of Motion Perceptionsupporting
confidence: 46%
See 2 more Smart Citations
“…It has been suggested that visuomotor control systems have spatiotemporal tunings different from those for motion perception (Amano et al 2007;Gomi et al 2006;. Indeed the present study showed directional dissociations between motion perception and OFRs, in particular for the CA-MSV stimuli, which can be ascribed at least partially to preference of the OFR responses to higher speeds.…”
Section: Comparison Between the Frequency Tuning Of Motion Perceptionsupporting
confidence: 46%
“…The frequency dependence of motion processing has been conventionally measured by contrast threshold, and it has been reported that it has a peak at a moderate spatial frequency (0.5-1 cpd) and moderate temporal frequency (5-10 Hz) (Burr and Ross 1982;Gomi et al 2006;Hutchinson and Ledgeway 2006). As an alternative way to measure contrast threshold, we proposed using a reverse correlation method to estimate the frequency tuning of motion processing above threshold.…”
Section: Low Spatial Frequency Preference For Supra-threshold Motion mentioning
confidence: 99%
See 1 more Smart Citation
“…3 A, B, solid curves), on the other hand, the hand trajectories deviated from the control as well. These deviations are also regarded as implicit visuomotor reactions (MFR) (Saijo et al, 2005;Gomi et al, 2006;Gomi, 2008). As shown in Figure 3A, these deviations of trajectories were readjusted in the later phase of reaching so that the reaching went to the center visible target.…”
Section: Resultsmentioning
confidence: 99%
“…During reaching movement, the hand can quickly adjust to target displacement (Soechting and Lacquaniti, 1983;Brenner and Smeets, 1997;Day and Lyon, 2000) even without perception of target location change (Goodale et al, 1986;Prablanc and Martin, 1992). Another type of quick and automatic reaction has also been observed when a surrounding visual motion is suddenly given during reaching, called the manual following response (MFR) (Brenner and Smeets, 1997;Whitney et al, 2003;Saijo et al, 2005;Gomi et al, 2006;Gomi, 2008). The reaction latencies of these two types of responses are much faster [100 -150 ms vs Ͼ250 ms for discrimination-reaction tasks (Anzola et al, 1977;Heister et al, 1986)], even though participants in the reaction tasks intently concentrated on detecting the stimulus onset.…”
Section: Introductionmentioning
confidence: 99%